Epicardial adipose and pre-sternal subcutaneous tissues associated with extent of pneumonia and hospitalization in COVID-19 - Sönmez Topcu, Feyza; Yurtlu Temel, Şirin (The European Research Journal, 2023)
Objectives: The aims of this study were, to analyze epicardial adipose tissue and pre-sternal adipose tissue thicknesses and the relationship of the ratio of these two parameters with radiological progression, age, gender, concomitant diseases, hospitalization, length of hospital stay, need for intensive care and survival status of COVID-19 patients. Methods: In this retrospective study, a total number of 204 PCR-positive COVID-19 patients, who have initial lung computed tomography (CT) and a second CT within 15 days due to prolonged symptoms or suspected complications were included. According to patterns of lung involvement at the time of diagnosis, patients were divided into 4 groups. In initial CT scans, epicardial adipose tissue and pre-sternal subcutaneous adipose tissue thickness were measured. Progression or regression of the disease is evaluated by comparing the findings in initial and control CTs. Results: The mean age, epicardial adipose tissue thickness (EAT), pre-sternal adipose tissue thickness (PAT), and the EAT/PAT ratio of patients with involvement in both lungs were found to be higher than those in patients with one lung or without lung involvement and there was a statistically significant positive correlation between them. Conclusions: This study is thought to be the first in which epicardial adipose tissue and pre-sternal adipose tissue were evaluated together in COVID-19 patients. Epicardial adipose tissue is a metabolically active organ and measurement in initial CT scans may give an easy and quick idea of the evolution of the disease.